2007
DOI: 10.1021/jo701944c
|View full text |Cite
|
Sign up to set email alerts
|

Hexakis(4-(N-butylpyridylium))benzene:  A Six-Electron Organic Redox System

Abstract: The cobalt-catalyzed cyclotrimerization of bis(4-pyridyl)acetylene affords hexakis(4-pyridyl)benzene in moderate yield. Alkylation with n-butyltriflate gives hexakis(4-(N-butylpyridylium))benzene triflate (1 6+), which can be reduced with Na/Hg in DMF to neutral 10. A single-crystal X-ray diffraction structure reveals that 1 0 has a chair-cyclohexane-like core and a [6]radialene structure. Cyclic voltammetry shows that 1 6+ is reversibly reduced to 1 2+ in one four-electron step and 1 2+ is reversibly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 32 publications
2
27
0
4
Order By: Relevance
“…The aromatic stabilization in the monocationic and dicationic forms was made responsible for their increased reduction power. 54 Another family of strong and neutral organic electron donors comprises viologens, which are easily oxidized to bipyridinium derivatives, and related compounds (like 'extended viologen' 55 and the reduced form of the hexacation hexakis [4-(N-butylpyridylium)]-benzene 56 (Figure 1). Murphy et al also synthesized bispyridinylidene compounds for use in the dehalogenation of aryl halides and other reactions.…”
Section: Redox-active Amines and Guanidinesmentioning
confidence: 99%
“…The aromatic stabilization in the monocationic and dicationic forms was made responsible for their increased reduction power. 54 Another family of strong and neutral organic electron donors comprises viologens, which are easily oxidized to bipyridinium derivatives, and related compounds (like 'extended viologen' 55 and the reduced form of the hexacation hexakis [4-(N-butylpyridylium)]-benzene 56 (Figure 1). Murphy et al also synthesized bispyridinylidene compounds for use in the dehalogenation of aryl halides and other reactions.…”
Section: Redox-active Amines and Guanidinesmentioning
confidence: 99%
“…[142] Recently, cyclic voltammetry of six-electron redox system 201 showed that 201 6+ is reversibly reduced to 201 2+ in one four-electron transfer and 201 2+ is reversibly reduced to 201 0 in one twoelectron transfer [E 1/2 (THF) = À0.58 and À0.69 V versus SCE; calibrated using Fc/Fc + ]. [143] Cyclic voltammetry of 202 showed a two-electron wave [E 1/2 (CH 3 CN) = À0.32 V versus SCE], although computational studies suggested that 202 could be a stronger two-electron reducing agent than 152 c in nonpolar solvents. [144] In other solvents, 152 c should be superior.…”
Section: Bispyridinylidenesmentioning
confidence: 99%
“…Fine‐tuning of the electrochemical properties of the dimers can be achieved by varying the following parameters:18a, 19 1) The interannular dihedral angle (that is, the degree of π delocalization),20 2) the connection scheme of the pyridinium rings, 3) the nature of the N pyridinio substituent (alkyl or aryl),14 and 4) the nature of the intervening linker (if any),21 which can even be switchable 22. The same approaches also hold for higher oligomers, even incorporating intervening spacers19 like star‐shaped tris‐23 and hexakis( p ‐ N ‐alkylpyridinium)benzene24 or other discrete entities like linear polypyridinium wires,25, 26 polyviologen dendrimers27 and rod‐like (1D) polymers 28. 29…”
Section: Introductionmentioning
confidence: 99%